2015
DOI: 10.4314/wsa.v41i3.08
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical reduction of pelletized gypsum mixed with carbonaceous reductants

Abstract: The recovery of better quality waste gypsum during acid mine drainage (AMD) neutralization is one step closer to achieving downstream waste gypsum beneficiation for recovery of valuable materials. This can facilitate recovery of treatment costs and prevention of environmental pollution from gypsum waste-dumps. Thermal reduction using rotary kilns to recover valuable materials from waste gypsum remains a critical and controversial process because of waste gypsum handling problems, environmental pollution due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…As reported by Yan et al (2014) and corroborated by Mbhele et al (2009) and Motaung et al (2015), temperature plays an important role in the conversion of the sulphate, with increasing temperature yielding an increased reaction ratewith. Mbhele et al (2009), who focused on the recovery of sulphur from waste gypsum using activated carbon, investigated several process conditions to determine their impact on the yield of CaS and subsequently sulphur.…”
Section: Calcium Sulphate Wastesupporting
confidence: 63%
See 2 more Smart Citations
“…As reported by Yan et al (2014) and corroborated by Mbhele et al (2009) and Motaung et al (2015), temperature plays an important role in the conversion of the sulphate, with increasing temperature yielding an increased reaction ratewith. Mbhele et al (2009), who focused on the recovery of sulphur from waste gypsum using activated carbon, investigated several process conditions to determine their impact on the yield of CaS and subsequently sulphur.…”
Section: Calcium Sulphate Wastesupporting
confidence: 63%
“…Several authors have reported that the thermal reduction process occurs via a gaseous intermediate, and can mostly likely be described by (Gorkan et al, 2000;Oh and Wheelock, 1990): [6] To this end, it has also been found that the presence of O₂ and CO₂ is undesirable as they favour the formation of calcium oxide and calcium sulphate. Thus, as reported by Jagtap, Pande, and Gokarn (1990), to effectively favour the formation of CaS from CaSO4 an excess of carbon monoxide (if using a gaseous reducing agent) should be present in the kiln; alternatively, if a solid reducing agent is used, an environment that favours excess amounts of CO in the kiln is desirable (Motaung et al, 2015).…”
Section: Calcium Sulphate Wastementioning
confidence: 92%
See 1 more Smart Citation
“…Outside China, water pollution caused by mineral processing has become a concern of experts in recent years. In 2015, Motaung, S. R. et al [42], researchers from South Africa, proposed that waste recovery and comprehensive utilization should be carried out in the process of beneficiation drainage and AMD so as to promote the recovery of treatment costs and prevent environmental pollution caused by gypsum waste dumping. In 2021, Malek, A.; Rao, G. R. and Thomas, T. [43], researchers from India, proposed that it is essential to remove heavy metals from wastewater before the discharge of beneficiation wastewater.…”
Section: Chemical Pollution Caused By Mining Operations and Productionmentioning
confidence: 99%